Menopause: focus on additional therapy opportunities. Literature review - О. О. Єфіменко; О. В. Занько (Publishing House TRILIST, 2020)
About 10% of the world's populations are menopausal women. This period coincides with the most active social and professional activities of almost every woman. In addition to typical manifestations, this age stage is characterized by menopausal metabolic syndrome, which is caused by estrogen deficiency and is found in 35-49% of women in older age groups. Modern approaches to the treatment and prevention of menopausal disorders include following principles: lifestyle changes, menopausal hormone therapy (MHT), non-hormonal therapy (drugs with hormone-like effects, phytoestrogens, selective modulators of estrogen receptors, β-alanine, sedatives, tranquilizers, and antidepressants), non-drug correction methods. According to the International Menopause Society recommendations (2016), MHT is a gold standard for prevention and treatment of menopausal disorders. However, the choice of MHT as a therapeutic standard is not always unambiguous and acceptable, because hormone therapy is associated with a number of side effects. In addition, there are a number of absolute contraindications for MHT. Therefore, the task of a gynecologist is to choose personalized (individual) therapy for menopausal disorders for each patient. Factors that must be considered when choosing between MHT and non-hormonal drugs include: severity and duration of menopause syndrome, presence of absolute and relative contraindications for MHT, patient's desire, tolerance of the chosen method. Phytoestrogens (selective modulators of plant-derived estrogen receptors, which are structurally similar to endogenous estrogens) are well-researched among the means of non-hormonal therapy of menopausal patients. Due to their weak estrogenic action, they reduce the severity of menopausal syndrome without affecting the proliferative processes in the endometrium. Phytoestrogens are used by gynecologists in many countries for mild climacteric complaints and/or if there are absolute contraindications for MHT. One of these drugs is Climona® that is contains biologically active components of plant origin (hop cones, cimicifuga root, dioscorea root, vitamin D, α-lipoic acid), which have been shown to be effective in decrease of menopause manifestations and reducing menopausal metabolic syndrome